2022
DOI: 10.1021/acs.inorgchem.2c02873
|View full text |Cite
|
Sign up to set email alerts
|

Two Neptunium(III) Mellitate Coordination Polymers: Completing the Series Np–Cf of Trans-Uranic An(III) Mellitates

Abstract: Two neptunium(III) mellitates, 237Np2(mell)(H2O)9·1.5H2O (Np-1α) and 237Np2(mell)(H2O)8·2H2O (Np-1β), have been synthesized from 237NpCl4(dme)2 by reduction with KC8 and subsequent reaction with an aqueous solution of mellitic acid (H6mell). Characterization by single-crystal X-ray crystallography and UV–vis–NIR spectroscopy confirms that the neptunium is in its +3 oxidation state and both polymorphs are isostructural to the previously reported plutonium mellitates. Of the two morphologies, Np-1α is indefinite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…8 Although curium is an actinide element, it has been shown that the later actinides in hard-donor coordination environments differ from lanthanides little in their structure and only slightly in pressure-induced changes of their electronic structure. 19,20,48 The predicted average bond length decrease of the Cm−O bonds was −0.008 Å/GPa, comparing well with the Ce−O bond length changes measured in this study.…”
Section: ■ Results and Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…8 Although curium is an actinide element, it has been shown that the later actinides in hard-donor coordination environments differ from lanthanides little in their structure and only slightly in pressure-induced changes of their electronic structure. 19,20,48 The predicted average bond length decrease of the Cm−O bonds was −0.008 Å/GPa, comparing well with the Ce−O bond length changes measured in this study.…”
Section: ■ Results and Discussionsupporting
confidence: 85%
“…The high-pressure structural changes of curium mellitate have also been examined computationally, albeit with a simplified trifluoroacetate molecules in place of the mellitate ligands . Although curium is an actinide element, it has been shown that the later actinides in hard-donor coordination environments differ from lanthanides little in their structure and only slightly in pressure-induced changes of their electronic structure. ,, The predicted average bond length decrease of the Cm–O bonds was −0.008 Å/GPa, comparing well with the Ce–O bond length changes measured in this study.…”
Section: Resultsmentioning
confidence: 69%
“…The bathochromic shift of MLCT of Bk1 correlates with a less positive oxidation potential to +4 compared to Cm 3+ and Cf 3+ (specifically, Bk 4+/3+ , + 1.3 V, 1 M HClO 4 , vs SHE.). 41 This spectroscopic trend of MLCT against oxidation potential is also observed in f-element hexa-halido complexes 56,57 and 58 Pu 3+ , 59 and Bk 3+14 ), where the MLCT transitions in the spectra occur at lower energies for the compound containing the actinide with a lower oxidation potential i.e. Np 3+ < Pu 3+ < Bk 3+ since Np 3+/4+ < Pu 3+/4+ < Bk 3+/4+ .…”
mentioning
confidence: 73%
“…. This spectroscopic trend of MLCT against oxidation potential is also observed in f-element hexa-halido complexes , and An 2 [C 6 (CO 2 ) 6 ]­(H 2 O) 8 ·2H 2 O (An 3+ = Np 3+ , Pu 3+ , and Bk3+ ), where the MLCT transitions in the spectra occur at lower energies for the compound containing the actinide with a lower oxidation potential i.e. Np 3+ < Pu 3+ < Bk 3+ since Np 3+/4+ < Pu 3+/4+ < Bk 3+/4+ .…”
Section: Resultsmentioning
confidence: 99%